2017
DOI: 10.1101/gad.303768.117
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3K4 methylation-dependent and -independent functions of Set1A/COMPASS in embryonic stem cell self-renewal and differentiation

Abstract: Of the six members of the COMPASS (complex of proteins associated with Set1) family of histone H3 Lys4 (H3K4) methyltransferases identified in mammals, Set1A has been shown to be essential for early embryonic development and the maintenance of embryonic stem cell (ESC) self-renewal. Like its familial relatives, Set1A possesses a catalytic SET domain responsible for histone H3K4 methylation. Whether H3K4 methylation by Set1A/COMPASS is required for ESC maintenance and during differentiation has not yet been add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
84
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 21 publications
5
84
2
Order By: Relevance
“…In contrast, there are only 300 misregulated genes in Mll4ΔSET cells compared with WT, suggesting that the primary functions of Mll4 in transcriptional regulation are catalytic-independent. This is consistent with our recent finding of the Mll3/Mll4 ortholog Trr in Drosophila , Set1A in mouse ESCs, and Set1B in human triple-negative breast cancer ( 12 , 20 , 31 , 48 ). We recently reported that the catalytically inactive Trr can rescue the embryonic lethality of Trr null alleles, demonstrating for the first time that enhancer H3K4me1 catalyzed by Trr is dispensable in the context of metazoan development ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, there are only 300 misregulated genes in Mll4ΔSET cells compared with WT, suggesting that the primary functions of Mll4 in transcriptional regulation are catalytic-independent. This is consistent with our recent finding of the Mll3/Mll4 ortholog Trr in Drosophila , Set1A in mouse ESCs, and Set1B in human triple-negative breast cancer ( 12 , 20 , 31 , 48 ). We recently reported that the catalytically inactive Trr can rescue the embryonic lethality of Trr null alleles, demonstrating for the first time that enhancer H3K4me1 catalyzed by Trr is dispensable in the context of metazoan development ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…This model presents a coherent explanation for the transition from repressed to open chromatin in keeping with our observed mutual exclusivity of the H3K27me3 mark and CFP1 binding. This model also places into context the evidence that in differentiated cells methyltransferase activity in bivalent domains switches from MLL2 to SET1A [ 54 ] and thus helps to broaden our view of key elements involved in gene regulation through chromatin modification. Further analyses of mutations in key proteins in this regulatory network will be necessary to expand on mechanistic insights into CFP1 functions.…”
Section: Discussionmentioning
confidence: 90%
“…The Set1-COMPASS complex is also essential for pluripotency through ensuring the continued expression of Oct4 (Bledau et al, 2014). Interestingly, Set1-COMPASS supports selfrenewal of ESCs in an H3K4 methyltransferase-independent manner (Sze et al, 2017). Similarly, the H3K4 methyltransferase activities of Trx-COMPASS (Ernst et al, 2004;Lubitz et al, 2007) and Trr-COMPASS (Wang et al, 2012 are dispensable for ESC self-renewal.…”
Section: Trxg Proteins In Stem Cellsmentioning
confidence: 99%
“…First, the Set1A-COMPASS complex functions in proliferating ESCs to prepare their eventual differentiation. It does this by ensuring that developmentally regulated genes are tri-methylated at H3K4 to create bivalently (H3K27me3/H3K4me3) marked promoters that are poised for activation upon differentiation (Sze et al, 2017). Upon differentiation, TF-dependent targeting of Trr-COMPASS complexes to enhancers of lineage-specific genes allows the activation of cell-specific gene expression programs .…”
Section: Trxg Proteins In Stem Cellsmentioning
confidence: 99%